THE EFFECT OF ANXIETY TOWARD STUDENTS’ LEARNING MOTIVATION OF THE ELEVENTH GRADE AT SMAN 4 PALU - hasriani; Abdul Gafur Marzuki; Yuni Amelia; Hijrah Syam (English Tadris Department, Faculty of Tarbiyah and Teacher Training, State Islamic University (UIN) Datokarama Palu, 2021)
The objective of this research was to investigate the effect of anxiety toward students’ learning motivation of the eleventh grade at SMAN 4 Palu in the academic year 2019- 2020. This research used as a survey quantitative research method. The population of this research was conducted for the eleventh-grade students of SMAN 4 Palu with consisted of 50 students, who used purposive sampling with took 2 classes as the samples to encourage representative data. In the procedure of collecting data, the researcher used one of instrument is questionnaire. The questionnaire used to encourage the effect of anxiety and the motivation in learning English of the students. The researcher was giving students a questionnaire using WhatsApp. The questionnaire in Google form, so students just open and checklist their answer and send. The result of the questionnaire has shown there was no significant effect of anxiety toward students’ learning motivation. This result of Pearson Product Moment table, which has shown were scores of Sigs between effect Anxiety and Motivation was 0,450 or more than 0,05. It means there was no effect of anxiety toward motivation. The researcher concluding the effect of anxiety toward students' learning motivation was normal.